Systematic review of the measurement properties of performance-based functional tests in patients with neck disorders. Issue 11 (24th November 2019) - McGee, Steven; Sipos, Taylor; Allin, Thomas; Chen, Celia; Greco, Alexandra; Bobos, Pavlos; MacDermid, Joy
Abstract : Objectives: The purpose of this systematic review is to identify and synthesise studies evaluating performance-based functional outcome measures designed to evaluate the functional abilities of patients with neck pain. Design: Systematic review. Data sources: A literature search using PubMed, Scopus, CINAHL, EMBASE, COCHRANE, Google Scholar and a citation mapping strategy was conducted until July 2019. Eligibility criteria: More than half of the study's patient population had neck pain or a musculoskeletal neck disorder and completed a functional-based test. Clinimetric properties of at least one performance-based functional tests were reported. Both traumatic and non-traumatic origins of neck pain were considered. Data extraction and synthesis: Relevant data were then extracted from selected articles using an extraction guide. Selected articles were appraised using the Quality Appraisal for Clinical Measurement Research Reports Evaluation Form (QACMRR). Results: The search obtained 12 articles which reported on four outcome measures (functional capacity evaluations (FCE), Baltimore Therapeutic Equipment Work Simulator II (BTEWS II), Functional Impairment Test-Hand and Neck/Shoulder/Arm (FIT-HaNSA)) and a physiotherapy test package, to assess the functional abilities in patients with mechanical neck pain. Of the selected papers: one reports content validity, five construct validity, four reliability, one sensitivity to change and one both reliability and construct validity. QACMRR scores ranged from 68% to 95%. Conclusions: This review found very good quality evidence that the FIT-HaNSA has excellent inter and intra-rater reliability and very weak to weak convergent validity. Excellent quality evidence of fair test-retest reliability, weak convergent validity and very weak known groups validity for the BTEWS II test was found. Good to excellent quality evidence exists that an FCE battery has poor to excellent reliability and very weak to strong validity. Good to excellent quality of weak to strong validity and trivial to strong effect sizes were found for a physiotherapy test package. Prospero registration number: CRD42018112358